MENGENALI FAKTOR-FAKTOR RISIKO PASIEN DIABETES MELITUS - Bagus Prakasa Sentosa (DiscoverSys Inc., 2016)
Background: Diabetes Mellitus (DM) remains a health problem in Indonesia as well as in many other countries.According to Medical Record of Regional Hospital of Karangasem Bali Province, the incidence of DM still highamong endocrine, nutrition and metabolic diseases. About 188 cases of DM had recorded in the year 2003, 221case in the year 2004 and 158 case in 2005. One of the strategies to decrease and manage this disease is bythe screening risk factors besides an adequate therapy.Objective: To assess the risk factors for DM such as age, family history of diabetes, dietary habits, knowledge about DM and type of personality amongst patient with DM.Methods: A case-control study was conducted on 154 patient from Regional Hospital of Karangasem Bali Province. Cases included 79 patient identified as a DM and controls include 75 patient who did not suffer DM.Data of age, family history of diabetes, dietary habits and type of personality was taken by questionnairediabetes risk factors. Data of risk factors was obtained by a questionnaire given to 2 groups (case and controlgroup).Results: There was association between several risk factors and incidence of DM, include; age [odds ratio(OR) = 6, 45; p= 0,000, PAR= 0, 84], family history of DM (OR= 3, 75; p = 0,001, PAR= 0, 73), knowledge about DM(OR= 0, 13; p = 0,000, PAR= -6, 7/as a protective factor). However, there was evidence of a no associationbetween type of personality and incidence of DM (OR= 50.4; p = 0,479, PAR= 0, 98) and also dietary habits (OR=1, 06; p = 0,896, PAR= 0 06)Conclusion: These findings suggest a complex interaction among age factor, family history of diabetes, knowledgeabout DM, dietary habits and type of personality with the incidence of DM in Regional Hospital of Karangasem Bali Province.